The Beethoven quartet companion - Winter, Robert, 1945-; Martin, Robert L., 1940- (University of California Press, 1994)
While the Beethoven string quartets are to chamber music what the plays of Shakespeare are to drama, even seasoned concertgoers will welcome guidance with these personal and sometimes enigmatic works. This collection offers Beethoven lovers both detailed notes on the listening experience of each quartet and a stimulating range of more general perspectives: Who has the quartets' audience been? How were the quartets performed before th.